2010
DOI: 10.3329/bmrcb.v33i3.1142
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity and pattern of viral hepatitis in clinically suspected cases of hepatitis in Dhaka city

Abstract: An attempt was made to see the seropositivity and pattern of four common hepatotrophic viruses (HBV, HCV, HEV, HAV) in patients suspected to have been suffering from viral hepatitis. Blood samples from 2,995 cases of suspected HBV infection, 331 from HCV, 155 from HEV and 24 from HAV were tested for these viral markers. Of these a total of 245 (8.1%) were positive for HBsAg, 18 (5.4%) for HCV, 87 (56.1%) for HEV and 8 (33.3%) were positive for HAV infection. The predominant age group affected in HBV is 25-40 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Studies from Dhakka, Bengladesh and Pakistan reported higher prevalence rates in males versus females 26,27.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Studies from Dhakka, Bengladesh and Pakistan reported higher prevalence rates in males versus females 26,27.…”
Section: Discussionmentioning
confidence: 93%
“…Prevalence of anti-HCV antibody in Uzbekistan was 2.2% in low-risk group 38; whereas, it was found to be 5.4% in 2,995 people from Dhaka, Bengladesh 24,26, and 4.56% in Romaine showing an urban distribution as 3.05% in Bucharest, 3.27% in Craiova and 6.37% in Constanta, and high rate in Constanta has been considered significant 25. Again in the same region in Italy, prevalence of anti-HCV antibody positivity was found 2.6% 32.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years viral hepatitis is a major public health problem worldwide. As with other Asian countries, Bangladesh is also hyper-endemic for HBV related liver disease, with seroprevalence of HBsAg is 6–7 % (Rahman et al 2007 ). However, data on genotype or subtype of HBV are not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on genotype or subtype of HBV are not sufficient. Some previous studies were conducted based on the serological assay where they have only shown the sero-prevalence HBV in Bangladesh (Rahman et al 2007 ; Zaki et al 2003 ). In this study, we have tried to find out the distribution of genotypes and subtypes in Bangladesh, because, genotyping and subtyping of HBV has its great implementation as HBV have their characteristic geographical distribution.…”
Section: Discussionmentioning
confidence: 99%